Manajemen Pemberdayaan Zakat dan Implikasinya terhadap Aspek Sosio Ekonomi dalam Kesejahtraan Umat - Rustandi, Ridwan; Abidin, Yusuf Zaenal; Rahman, Arif; Yuliani, Yuliani (Tadbir: Jurnal Manajemen Dakwah, 2023)
The welfare of the people in the Islamic perspective includes material, moral, and spiritual welfare. This view is in line with human nature which is holistic in nature which has implications for the socio-economic system of society which cannot be separated from all Islamic teachings in an integral and comprehensive manner. To realize this welfare, efforts are needed, one of which is through empowerment and professional zakat management. Through professional management, zakat is a potential source of funds that can be used to achieve general welfare for the whole community in Indonesia. Good and professional zakat management using modern management principles is expected to increase the dignity of the Islamic community from underprivileged conditions, as well as escape the trap of poverty and economic backwardness. Management of zakat empowerment can be manifested as well-organized zakat management activities which consist of planning, organizing, implementing, and controlling or supervising carried out to achieve the goal of utilizing the potential of zakat that has not been maximized in Indonesia through the utilization of human resources and other resources which ultimately have an impact on the socio-economic aspects of the welfare of the people.